Phase III randomized, double‐blind study of paclitaxel with and without everolimus in patients with advanced gastric or esophagogastric junction carcinoma who have progressed after therapy with a fluoropyrimidine/platinum‐containing regimen (RADPAC). Issue 9 (7th May 2020) - Lorenzen, Sylvie; Knorrenschild, Jorge Riera; Pauligk, Claudia; Hegewisch‐Becker, Susanna; Seraphin, Jörg; Thuss‐Patience, Peter; Kopp, Hans‐Georg; Dechow, Tobias; Vogel, Arndt; Luley, Kim Barbara; Pink, Daniel; Stahl, Michael; et al.
Abstract: The RADPAC trial evaluated paclitaxel with everolimus in patients with advanced gastroesophageal cancer (GEC) who have progressed after therapy with a fluoropyrimidine/platinum‐containing regimen. Patients were randomly assigned to receive paclitaxel (80 mg/m 2 ) on day 1, 8 and 15 plus everolimus (10 mg daily, arm B) d1‐d28 or placebo (arm A), repeated every 28 days. Primary end point was overall survival (OS). Efficacy was assessed in the intention‐to‐treat population and safety in all patients who received at least one dose of treatment. This trial is registered with ClinicalTrials.gov, number NCT01248403. Between October 2011 and September 2015, 300 patients (median age: 62 years; median lines prior therapy: 2; 47.7% of patients had prior taxane therapy) were randomly assigned (arm A, 150, arm B, 150). In the intention to treat population, there was no significant difference in progression‐free survival (PFS; everolimus, 2.2 vs placebo, 2.07 months, HR 0.88, P = .3) or OS (everolimus, 6.1 vs placebo, 5.0 months, HR 0.93, P = .54). For patients with prior taxane use, everolimus improved PFS (everolimus, 2.7 vs placebo 1.8 months, HR 0.69, P = .03) and OS (everolimus, 5.8 vs placebo 3.9 months, HR 0.73, P = .07). Combination of paclitaxel and everolimus was associated with significantly more grade 3‐5 mucositis (13.3% vs 0.7%; P < .001). The addition of everolimus to paclitaxel did not improve outcomes in pretreated metastatic gastric/gastroesophageal junction (GEJ) cancer. Activity was seen in the taxane pretreated group. Additional biomarker studies are planned to look for subgroups that may have a benefit. Abstract : What's new? Patients with advanced gastroesophageal cancer who fail first‐line chemotherapy regimens often suffer poor prognosis in later rounds of therapy. A promising therapeutic strategy for these patients entails targeting the PI3K‐Akt‐mTOR pathway with everolimus. Here, in a randomized, double‐blind phase III study, the chemotherapeutic agent paclitaxel was tested with or without everolimus in patients with advanced gastroesophageal cancer. For most patients, everolimus had no significant impact on survival. Survival benefits were observed, however, for certain patient subgroups, namely patients previously treated with taxanes who might not be candidates for paclitaxel and ramucirumab combination therapy after failure of first‐line platinum therapy.